2009
DOI: 10.1007/s11999-008-0683-8
|View full text |Cite
|
Sign up to set email alerts
|

Ponseti Treatment for Idiopathic Clubfoot: Minimum 5-year Followup

Abstract: Ponseti clubfoot treatment has become more popular during the last decade. We reviewed the medical records of 74 consecutive infants (117 club feet) who underwent Ponseti treatment. Minimum followup was 5 years (mean, 6.3 years; range, 5-9 years). We studied age at presentation, previous treatment, the initial severity score of the Pirani scoring system, number of casts, need for Achilles tenotomy or other surgical procedures, and brace use. We measured final ankle motion and parents' perception of outcome. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
117
3
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 31 publications
14
117
3
9
Order By: Relevance
“…Bor et al [2] observed that deviations from the Ponseti bracing recommendations were associated with a near twofold increase in additional operations. Excessive weight gain [4], parental educational level [8,12], a positive family history [8,12], and bracing noncompliance [8,9,11,21,28,31] have been identified as patient-related predictors of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Bor et al [2] observed that deviations from the Ponseti bracing recommendations were associated with a near twofold increase in additional operations. Excessive weight gain [4], parental educational level [8,12], a positive family history [8,12], and bracing noncompliance [8,9,11,21,28,31] have been identified as patient-related predictors of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were comparable to the joint-sparing treatment group. Bor et al [9] reported on 74 clubfoot patients treated with the Ponseti method with a mean age of 6.3 years (five to nine years) with a DSI being available for 68 of those patients. Unfortunately, the total score was not reported which makes a direct comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, initial results in patients treated outside of Iowa have been very promising in many centres and in different countries [6][7][8]. Only a few study groups outside of Iowa describe midterm outcomes of the Ponseti method, with generally very favourable results [9][10][11]. On the other hand high rates of recurrence [12,13] and the need to surgically correct persistent deformities [14] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…93,94,106 Figure 2 illustrates a case treated by the Ponseti method. The Ponseti method is being widely publicized, both in developed countries and in those under development [107][108][109][110][111][112] , on account of the good correction rates achieved, which are close to 90% 4,60,95,113,114 , while in Kite's technique, around 50% of cases require surgical intervention and around 40% present residual deformity. 115 Another important factor is that the treatment time with Kite's technique is approximately twenty-two months, while with the Ponseti method, the time is from two to four months.…”
Section: Ponseti's Methodsmentioning
confidence: 99%
“…Tenotomy is indicated when the hindfoot does not attain 15˚ of dorsiflexion, after achieving varus and adduction correction, and is necessary in 70 to 90% of patients. 1,4,95,114,[117][118][119] Attempts at forced correction of equinus with plaster produces the classical "rocker-bottom" deformity. Furthermore, relapses after treatment can be frequent and are part of the actual natural history of the disease.…”
Section: Ponseti's Methodsmentioning
confidence: 99%